Single Atoms in Photocatalysis: Low Loading Is Good Enough! - Qin, Shanshan; Will, Johannes; Kim, Hyesung; Denisov, Nikita; Carl, Simon; Spiecker, Erdmann; Schmuki, Patrik (ACS Energy Letters, 2023)
We disperse Pt single atoms (SAs) with different loading densities on anatase TiO2 thin films and evaluate the photocatalytic H2 generation as a function of the incident light intensity. We show that under common illumination intensities (such as terrestrial solar illumination), a minuscule Pt SA loading of ∼105 atoms μm-2 (surface Pt content ∼0.1 at.%) is sufficient to achieve a maximized H2 production rate. This results in a maximum turnover frequency at a single Pt atom site of ∼300 H2 molecules s-1. For a vast majority of illumination conditions and a suitable surface configuration, it is not the density of co-catalytic sites that is rate-determining (a high loading is not needed!), but the charge carrier generation (and flux of photoelectrons to the co-catalytic centers) determines the overall reaction rate. This is in stark contrast to SA catalysis of classic chemical reactions where generally a maximum loading of reactive SA delivers a maximum activity.
CRIS-Team Scopus Importer:2023-02-10